Indonesian medicinal plants' therapeutic potential against dengue virus infection: A literature review - Kartika, Aisya Alma Asmiranti; Dewi, Beti Ernawati; Sudiro, Tjahjani Mirawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Infections caused by the dengue virus (DENV) exhibit a wide range of clinical manifestations, from asymptomatic cases to severe, and sometimes life-threatening, conditions. Therefore, identifying effective antivirals and anti-inflammatory agents is a promising strategy to reduce the impact of these infections. Indonesia, with its rich biodiversity, particularly in medicinal plants, offers potential sources for such treatments. Most research on DENV antivirals in Indonesia has been conducted in vitro and has predominantly focused on DENV serotype 2 (DENV-2). However, in vivo research on medicinal plants, as well as studies on their anti-inflammatory properties, remains limited in Indonesia.Extracts that have been investigated in both in vivo and in vitro settings are limited to Cassia alata and Curcuma longa. Plants possessing antiviral properties originate from diverse botanical families, with leaves being the most utilized plant component. Flavonoids are found in most medicinal plants that have antiviral properties. Indonesia is known to have other natural compounds, including quercetin, isobutyl gallate, curcumin, and 6-gingerol, which have antiviral properties. Curcumin and 6-gingerol are the only natural compounds that have been subjected to testing against all four serotypes of dengue. This article provides a comprehensive review of medicinal plants in Indonesia, focusing specifically on their therapeutic potential against the dengue virus.